BLOOD STORAGE ANALYSIS OF HEMOGLOBIN ERYTHROCYTE AND PLATELET LEVELS IN WHOLE BLOOD COMPONENTS 0 DAYS 7 DAYS UP TO 15 DAYS AND 30 DAYS AT THE INDONESIAN RED CROSS (PMI) BLOOD DONATION UNIT (UUD) SEMARANG REGENCY - Riadi, Ahmad Riadi; Kahar, Fitriani; widodo, Widodo; Aprianti, Dina; Margi Rahayu, Umi (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2023)
During the storage process, blood will experience changes in blood components such as hemoglobin levels. The longer blood is stored, the more red blood cells will be destroyed because blood that is stored for too long will experience a shift in the oxygen dissociation curve to the left. The aim of this study was to determine the effect of blood storage on the levels of platelets, erythrocytes and hemoglobin in the whole blood component of blood for 0 days, 7 days, 15 days and 30 days at the blood donor unit (UUD) of the Indonesian Red Cross (PMI) Semarang Regency. The type of research used is descriptive research, where this research aims to describe or provide an overview of the effect of storing blood in whole blood components on changes in platelet, erythrocyte and hemoglobin levels in PMI Semarang Regency. The population and research samples are donors in PMI Semarang Regency. Data analysis: Data processing is carried out by: Editing, namely selecting and correcting hemoglobin level data collected from the measurement results during each experiment. Tabulating is the presentation of research data in the form of tables of Hemoglobin reading results or descriptive or analytical analysis results. Processing is the activity of processing data so that it can be analyzed by entering data on hemoglobin levels. Cleaning or data checking is checking the hemoglobin level data that has been entered again to see if there are errors or not